2016
DOI: 10.1097/won.0000000000000235
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After Ostomy Surgery in Muslim Patients

Abstract: Muslims requiring ostomies should receive preoperative counseling by surgeons and ostomy nurses. These discussions should also include faith leaders and/or hospital chaplains. Ongoing support after surgery can be extended into the community and encompass family doctors and faith leaders. Additional research exploring HRQOL after surgery in Muslims living in Western societies is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 34 publications
0
25
1
8
Order By: Relevance
“…18 It has been shown that these can be more problematic for patients of the Islamic faith. 6,18 Muslims with an ostomy, and especially elderly, socially deprived or persons with lower educational levels, may require a more focused follow-up to assess general well-being and coping after stoma surgery. 19 Therefore, health status and coping after stoma formation should be followed in a tailored manner for this cohort of patients.…”
Section: Medical Guidance For Healthcare Professionalsmentioning
confidence: 99%
See 4 more Smart Citations
“…18 It has been shown that these can be more problematic for patients of the Islamic faith. 6,18 Muslims with an ostomy, and especially elderly, socially deprived or persons with lower educational levels, may require a more focused follow-up to assess general well-being and coping after stoma surgery. 19 Therefore, health status and coping after stoma formation should be followed in a tailored manner for this cohort of patients.…”
Section: Medical Guidance For Healthcare Professionalsmentioning
confidence: 99%
“…Hence, community education of Muslim patients living with an ostomy, in collaboration with faith institutions, hospital-based spiritual leaders, and medical staff can have significant and sustained benefits following stoma surgery. 6 However, when the stoma contents do exit the bag then the wudhu would be invalidated. 19 It is not prohibited for a person with a stoma bag to enter a mosque or to perform Tawaf (circumambulation of the Kaba during Hajj), on the condition that they are sure that they will not soil the mosque and there is no unpleasant odour which could inconvenience other worshippers.…”
Section: Medical Guidance For Healthcare Professionalsmentioning
confidence: 99%
See 3 more Smart Citations